BLACK COLORATION ON THE OLFACTORY SACS OF SCOLlODON CAUGHT OFF BOMBAY - Ghate, H V (Indian Journal of Fisheries, 2011)
The frozen sharks come to Pune from the Bombay market and are presumablycaught off Bombay. Owing to long storage in ice. the detailed histologicalpicture was difficult to obtain. Studies on freshly collected sharks arenecessary to understand the basis of this pathological condition and to knowwhether it has any relation with water quality.